El paisaje urbano de Zaruma de la segunda década del siglo xxi, 2019 - 2020, con una visión pictórica impresionista - Pineda Zhuni, Elvis Alejandro (2020)
The present investigation entitled The urban landscape of Zaruma of the second decade of the 21st century, 2019-2020, with an impressionistic pictorial vision, develops a theoretical-practical work, the representation of the elements that make up nature: mountains, plants, sky, clouds, streets, etc., and integrate the architecture of the city to carry out pictorial works. During this artistic process the deductive method was used, establishing general concepts about the impressionist landscape, colonial architecture, as well as from the artistic experience in the inductive to apply the knowledge obtained in the course of academic training. Claude Monet, Camille Pissarro and Auguste Renoir were chosen as references, to understand and analyze the impressionist style, which allowed the production of the works to be developed, the managerial motif used was the urban landscape of Zaruma, taking the heritage as a reference cultural of the historic mining city, to which the citizens of the town give great importance, preserving the architecture of their homes. In this way the author made paintings of the place, which will serve as inspiration to revalue the landscape as a genre and other impressionist painters that are booming in the 21st century.